Preventive Approach to Unsubstantiated Claims and Disputes in the UK Construction Industry - Nosheen, Asia; Arewa, Andrew Oyen; Akhtar, Hafiz Muhammad (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Globally, claims and disputes are an unfortunate reality in construction projects. Recent statistics reveal that construction claims in the UK increased by 21% in 2018 compared to other countries such as India (8%), Mexico (3%), Ireland (2%), and Cyprus (2%). Though, construction industry is known for array of standard forms of contract and administrative tendencies; unsubstantiated claims and chronic disputes remain prevalent in the sector. Yet, there is little research on preventive approach to unsubstantiated claims that ultimately lead to disputes. The study advocates the use of Systematic and Technical Appraisal (STA) to prevent unsubstantiated claims and disputes in the construction industry. The study research method is based on qualitative research technique and use of case studies. The research question is: does systematic and technical appraisal of construction claims help prevent unsubstantiated claims and disputes in the UK construction industry? The study population sample is drawn from experienced industry stakeholders including clients, contractors, consultants, experienced quantity surveyors and cost managers in addition to use of construction case studies. Initial findings reveal that claim management processes in the construction sector are far-off from perfection. Other findings reveal that robust systematic and technical claim appraisal process has potential to prevent unsubstantiated claims; which in most cases lead to disputes. The study is part of an on-going PhD study to seek to develop an effective claim management system for the UK construction industry.